Predictors of oral healthcare utilization and satisfaction among Indian migrants and the host population in the Netherlands - Amandeep Pabbla; Denise Duijster; Irene H. A. Aartman; Charles Agyemang (BMC Oral Health)
Abstract Background The aim of this study was to explore predictors associated with reasons for visiting an oral healthcare professional (OHP) and satisfaction with OHPs in the Netherlands among the Indian migrants and the host population. Methods A random sample was obtained for this cross-sectional questionnaire study. Variables were classified according to the Andersen Behavioural Model of Health Services Utilization. Multivariable binary logistic regression analysis was conducted to identify significant predictors for reasons for visiting an oral healthcare professional (OHP) (routine checkups and preventive care or visiting only for pain and/or treatment) and satisfaction with OHPs (satisfied or dissatisfied). Results The sample consisted of 391 participants (Indian migrants = 147 and host population = 244). Indian migrants with higher internal locus of control (LoC) [OR = 7.73 (95% CI: 2.13;27.99)], more trust in OHPs [OR = 4.12 (95% CI:1.68;10.14)] and higher integration level [OR = 1.09 (95% CI:1.03;1.17)] had higher odds of visiting an OHP for routine checkups and preventive care. In the host population, having dental insurance [OR = 2.64 (95% CI:1.00;6.95)] was significantly associated with increased odds of visiting an OHP for routine checkups and preventive care. For satisfaction, Indians with low paid jobs [OR = 16.26 (95% CI:2.83;93.36)] and those with higher integration levels [OR = 1.29 (95% CI:1.16;1.42)] had higher odds of being satisfied with the Dutch OHPs. Among the host population, those with more trust in OHPs [OR = 2.86 (95% CI:1.19;6.88)] had higher odds of being satisfied. Conclusion Our study emphasize that integration levels and trust emerged as two crucial factors, policy makers can leverage upon to improve access to care for Indian migrants. Clinical trial N.A as this is a survey based cross sectional study.